Relaxor behavior of (Ba,Sr)(Zr,Ti)O-3 ferroelectric ceramics - Chew, Khian Hooi; Chan, H.L.W.; Tang, X.G.; Wang, X.X. (2005)
We examine the ferroelectric-relaxor behavior of (Ba0.65Sr0.35)(Zr0.35Ti0.65)O-3 (BSZT) ceramics in the temperature range from 80 to 380 K. A broad dielectric maximum, which shifts to higher temperature with increasing frequency, signifies the relaxor-type behavior of these ceramics. The value of the relaxation parameter gamma similar to 2 estimated from the linear fit of the modified Curie-Weiss law, indicates the relaxor nature of the BUT ceramics. The dielectric relaxation rate follows the Vogel-Fulcher relation with T-VF=107 K, E-a=0.121 eV, and nu(o)=6.83 X 10(14) Hz, further supports such relaxor nature. The slim P-E hystecesis loop and `butterfly' shape do bias field dependence of permittivity at T>T-m (T-m, the temperature of permittivity maximum) clearly signifies the occurrence of nanopolar clusters, which is the typical characteristic of ferroelectric relaxor. At 300 K and 10 kHz, the dielectric constant and loss tan delta are similar to 1100 and 0.0015, respectively. The high tunability (similar to 25%) and figure of merit (similar to 130) at room temperature show that the BSZT ceramics could be a promising candidate for tunable capacitor applications. (C) 2005 Elsevier Ltd. All rights reserved.